2021
DOI: 10.1109/access.2021.3077287
|View full text |Cite
|
Sign up to set email alerts
|

A GPU-Accelerated Modified Unsharp-Masking Method for High-Frequency Background- Noise Suppression

Abstract: A digitized analog signal often encounters a high-frequency noisy background which degrades the signal-to-noise ratio (SNR) particularly in case of low signal strength. Despite quite a lot of hardware-and software-based approaches have been reported to date to deal with the noise issue, it is still a challenging task to real-time retrieve the noise-contaminated low-frequency information efficiently without degrading the original bandwidth. In this paper, we report a modified unsharp-masking (UM)-based Graphics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Qianjiao Wu et al [29] CUDA algorithm improved the computational efficiency of multiscale DEM analysis, reducing response times.Engels et al [30]'s CUDA-SHAPE algorithm and Axel Davy et al [31] GPU-accelerated denoising solution both enhanced the performance of their respective software and algorithms. The works of Bhaskar Jyoti Borah et al [32] and Dariusz Puchala and Kamil Stokfiszewski [33] further demonstrated the effectiveness of GPU acceleration in image processing.Tianru Xue et al [34] real-time anomaly detection technology and Raghav G. Jha et al [35] TRG accelerated computation method, along with Qiyang Xiong et al [36] PIC simulation optimization scheme, all showcase the potential of GPUs in enhancing remote sensing data processing capabilities. These studies provide new directions for efficient processing of remote sensing data.…”
Section: Introductionmentioning
confidence: 96%
“…Qianjiao Wu et al [29] CUDA algorithm improved the computational efficiency of multiscale DEM analysis, reducing response times.Engels et al [30]'s CUDA-SHAPE algorithm and Axel Davy et al [31] GPU-accelerated denoising solution both enhanced the performance of their respective software and algorithms. The works of Bhaskar Jyoti Borah et al [32] and Dariusz Puchala and Kamil Stokfiszewski [33] further demonstrated the effectiveness of GPU acceleration in image processing.Tianru Xue et al [34] real-time anomaly detection technology and Raghav G. Jha et al [35] TRG accelerated computation method, along with Qiyang Xiong et al [36] PIC simulation optimization scheme, all showcase the potential of GPUs in enhancing remote sensing data processing capabilities. These studies provide new directions for efficient processing of remote sensing data.…”
Section: Introductionmentioning
confidence: 96%
“…Zhu 20 proposed an improved self-adaptive UM image enhancement algorithm, which improves the operation speed of the algorithm. Borah et al 21 proposed an improved GPU-based UM acceleration algorithm, which effectively suppresses the high-frequency noise background in the image and improves the execution speed of the algorithm.…”
Section: Related Research Introductionmentioning
confidence: 99%